Transcatheter Closure of a Large Muscular Ventricular Septal Defect (VSD) in a Child Weighing Five Kilogram with Severe Pulmonary Arterial Hypertension - Fatema Begum, Nurun Nahar (Journal of Armed Forces Medical College, Bangladesh, 2021)
Ventricular septal defect (VSD) is the commonest congenial heart lesion which may close spontaneously in significant number of cases. Muscular VSD has better chance of spontaneous closure. Some of the large muscular VSDs may cause severe complications like pulmonary hypertension and intractable heart failure. Closing VSD in young infant is challenging specially with devices as delivery systems are too large comparing to size of femoral vessels. Some centre prefers hybrid procedure of per ventricular device closure as surgical closure is high risk in young infants with complications. Here a case of large muscular VSD with severe pulmonary hypertension is reported in a ten month old girl which was closed successfully with a Konar- MFTM device and patient was discharged after 24 hours. JAFMC Bangladesh. Vol 16, No 2 (December) 2020: 84-86